1998
DOI: 10.1542/peds.102.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Educational Disabilities of Neonatal Intensive Care Graduates

Abstract: Educational disabilities of NICU graduates are influenced differently by perinatal and sociodemographic variables. Researchers must take into account both sets of these variables to ascertain the long-term risk of educational disability for NICU graduates. Birth weight alone should not be used to assess NICU morbidity outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 49 publications
5
37
0
3
Order By: Relevance
“…After 1 year, the biologic factors have reduced impact on development while socioeconomic factors predominate. 37,38 The home environment was the most influential factor of the variables studied in terms of mental development. Therefore, its effect on the long-term development of premature infants from low socioeconomic status backgrounds is of interest for future studies.…”
Section: Discussionmentioning
confidence: 98%
“…After 1 year, the biologic factors have reduced impact on development while socioeconomic factors predominate. 37,38 The home environment was the most influential factor of the variables studied in terms of mental development. Therefore, its effect on the long-term development of premature infants from low socioeconomic status backgrounds is of interest for future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers have found associations with both perinatal and sociodemographic factors and mental deficiencies and specific learning difficulties; although sociodemographic factors appear to be primarily associated with emotional disturbances and specific learning difficulties. 49 Other authors 50 …”
Section: Final Considerationsmentioning
confidence: 99%
“…1,2 Preterm birth may pose risks to learning through cognitive and behavioral disorders, especially due to perception, attention and hyperactivity disorders. [3][4][5][6] Bhutta et al demonstrated that preterm infants have lower cognitive scores than full-term controls, which are correlated with birthweight and gestational age. 2 According to Silbertin et al, 7 cognitive disorders in general are observed at a later stage and are grouped into developmental disabilities and disorganization disorders that affect mainly cognitive functions, such as memory and/or language, and that may be associated with psychomotor instability.…”
Section: Introductionmentioning
confidence: 99%